Increasing The Role As Well As Communities In The Construction of Forest Fire Through The Strengthening of Individual Institutions In Muaro Jambi District - Syarif, Afif; Fitria, Fitria (Jurnal Karya Abdi Masyarakat, 2019)
Disasters of forest and land fires accompanied by smoke disasters that hit Jambi Province especially in Muaro Jambi Regency have an impact on the health, environment and economy of the people both in Indonesia and in neighboring countries, Malaysia and Singapore. This legal counseling aims to describe and analyze the strengthening of customary institutions in the prevention and control of forest and land fires in Muaro Jambi District. This legal extension uses a type of descriptive approach with a qualitative approach. The focus of this legal counseling is the strengthening of indigenous peoples' institutions in the prevention and control of forest and land fires. The expected outcome of this legal counseling is the strengthening of indigenous peoples' institutions in the prevention and control of forest and land fires that have not been effective. The advice given is in fire control should be at the stage of prevention of preventive and repressive measures in the enforcement of environmental law against forest and land burning in Muaro Jambi district.